ANALISIS STRATEGI INSTALASI PENGELOLAAN LOGISTIK PADA JASA PELAYANAN KESEHATAN - Sri Hermayanti; Dina Indah Pertiwi; Ashady Hanafie (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Health services are business units that provide health services. One important aspect of health care services is logistics. The availability of logistics is a demand for maximum service, both medical and non-medical logistics. The importance of a logistics management strategy can help maximize services from health service providers. The purpose of this research is to describe the logistics management strategy plan for XYZ health services. The method used is a case study approach to Strength-Weakness-Opportunity-Threat (SWOT) analysis. Data collection was carried out in October 2022 through document review and interviews. The results obtained for the IPL position were in cell II, growth and building with an EFE score of 3.00 and IFE 2.75. The formulation of the chosen strategy is focused on increasing the cooperation that was previously established with goods and service providers, creating an integrated management information system in units related to the Logistics Management Installation (IPL) and adding storage space